2018
DOI: 10.1177/2167696818810268
|View full text |Cite
|
Sign up to set email alerts
|

Do Institutional Characteristics Predict Markers of Adulthood?: A Close Replication of Fosse and Toyokawa (2016)

Abstract: Recent research reveals that some variability in personality differences can be explained by contextual factors such as location. Although little research has systematically evaluated how such variables predict individual differences in Emerging Adulthood, Fosse and Toyokawa (2016) revealed that characteristics of one’s university such as selectivity and liberal arts classification did predict respondents’ perceived importance and attainment of milestones associated with adulthood. As a close replication of Fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It has also been found that people with higher education are more prone to perceive EA as a time for identity exploration and experimentation (Ismyrlis, 2021; Mattys et al, 2021). Differences in education fields may also influence income opportunity as well as lifestyle, contributing to observed differences in the perception of EA between people with different types of degrees (Fosse & Toyokawa, 2016; Grahe et al, 2020).…”
Section: Higher Educationmentioning
confidence: 99%
“…It has also been found that people with higher education are more prone to perceive EA as a time for identity exploration and experimentation (Ismyrlis, 2021; Mattys et al, 2021). Differences in education fields may also influence income opportunity as well as lifestyle, contributing to observed differences in the perception of EA between people with different types of degrees (Fosse & Toyokawa, 2016; Grahe et al, 2020).…”
Section: Higher Educationmentioning
confidence: 99%
“…When data have a hierarchical structure (e.g., individuals nested within institutions), residuals within statistical analyses may be dependent due to institution-level variability (Geldhof, Preacher, & Zyphur, 2014). This issue arises because participants within a particular institution may have similarities to one another leading to confounding by institution (a question addressed from a theoretical perspective by Grahe et al (2020).…”
Section: Analysis Planmentioning
confidence: 99%
“…Although there were certainly some bumps along the road, the project generally indicated to us that registered reports with secondary data are not only possible but that they are desirable. Some of the considerations that arose in the five papers in this collection included how to fit measurement models (Faas et al, 2020), conducting power analyses when using subgroups of unknown size (Chalk et al, 2020), analyses based on multilevel models when the amount of variance at each level is not known (Grahe et al, 2020), creating a reasonable set of alternative models to compare to the target model (Barlett et al, 2020), and creating indices from items without knowing how well they will hang together (Leighton et al, 2020). In all cases, authors needed not only to rely on the best possible prior information to make informed decisions but also to think through different contingency plans if that prior information did not comport with reality.…”
mentioning
confidence: 99%